Phytochemical analysis, antioxidant, and antitumor activity of Ligustrum ovalifolium leaves grown in Jordan: an in vitro and in vivo study - Asma Ismail Mahmod; Muna Oqal; Ali Muharrif Khalid; Fatma U. Afifi; Wamidh H. Talib (Pensoft Publishers, 2024)
Ligustrum ovalifolium (family Oleaceae) is a flowering plant with reported anti-inflammatory, antioxidant, hypotensive, and hypoglycemic activities. The present study investigated the phytochemical components and biological activities of L. ovalifolium leaves. Results showed that ethyl acetate extract has the highest potential to reduce cell growth in HeLa, T47D, and MDA-MB-231 cell lines with IC₅₀ values of 0.047, 0.07, and 0.072 mg/mL, respectively. Based on the LD50 value, the tumor-bearing mice were IP injected with 12.5 mg/kg of ethyl acetate extract. Tumor growth was significantly reduced (-43.1%) compared to the control group. According to the LC-MS analysis, Apigenin-7-O-glucoside was the flavonoid with the highest percentage value in L. ovalifolium leaves. DPPH assay exhibited antioxidant activity of ethanol and water extracts with the percentage of scavenging around 91% at a concentration of 200 µg/mL. As well, the assessment of liver and kidney functions of the experimented animals showed no toxicity effect compared to the control result. All things considered, the outcomes of this study revealed an antitumor potential of L. ovalifolium leaves extracts, hence this activity may arise from the presence of different potent flavonoids and the antioxidant potential. Nevertheless, further investigations are needed to determine the targets and signaling pathways that are affected by L. ovalifolium leaves extracts.